KEILAHIAN DAN KEMANUSIAAN KRISTUS DALAM PERISTIWA KELAHIRANNYA - Gustin Gustin; Tafparel Paskcea Jordanyya Elkenans; Vela Velia Candradinata; Sarmauli (Adisam Publisher, 2025)
This study aims to describe the understanding of Christological doctrine regarding the unity of Christ's divinity and humanity in the event of His birth, examine the relationship between incarnation and salvation, and understand its practical implications as a model of faith, hope, and service. This research uses a qualitative approach by reviewing literature from five book sources and five online journals. The results show that Christological doctrine explains the unity of divinity and humanity through the concept of incarnation established by the church councils. The birth of Christ through the Virgin Mary proves His humanity, while conception through the Holy Spirit demonstrates His divinity. Incarnation has an integral relationship with salvation; without it, the work of redemption cannot be accomplished because a perfect Mediator with both divine and human nature is required. Furthermore, the birth of Jesus provides an example of humility that serves as the foundation for the faith, hope, and service of Christians today. This research concludes that the event of Christ's birth is not merely historical but a fundamental theological foundation for the Christian faith, with relevant implications for the life and ministry of believers.